Analisis Optimasi Keuntungan Produksi Menggunakan Program Linier Metode Simpleks pada Kasus Maksimasi di UMKM Lumpia Basah & Kwetiau Van Java - Raisa Rahmania; Risma Febriyanti; Suci Rahma Putri; Somadi Somadi (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This research was motivated by the limited availability of raw materials faced by Lumpia Basah & Kwetiau Van Java MSME in determining the optimal production quantity to maximize profit. Inappropriate production planning may lead to inefficient utilization of available resources. This study aims to determine the optimal production combination of Lumpia Basah and Kwetiau using Linear Programming with the Simplex Method. The research employed a descriptive quantitative approach. Primary data were obtained through observation and interviews with the business owner, while secondary data were collected through a literature review of relevant books and scientific journals. The decision variables in this study were the production quantities of Lumpia Basah and Kwetiau, with the objective of maximizing profit. The constraints consisted of the limited availability of eggs, bean sprouts, and Chinese cabbage as raw materials. The model was solved mathematically using the Simplex Method and validated using POM-QM for Windows software. The results showed that the optimal production combination was 33 packs of Lumpia Basah and 116 packs of Kwetiau per day, generating a maximum daily profit of IDR 483,120. Both the mathematically calculation and the POM-QM for Windows software produced identical results, indicating that the Simplex Method is effective as a decision-making tool for production planning to improve raw material utilization efficiency and maximize the profitability of MSMEs.